LEARNER AUTONOMY AS ONE OF THE SIGNIFICANT APPROACHES IN ENGLISH LEARNING COURSES (Konferensiyalar | Conferences, 2024)
Because learner autonomy is associated with the effective development of students' communication abilities in foreign language curricula, it has gained significant attention in recent years. Furthermore, since its inception, learner autonomy has been strongly linked to emerging technologies.